Take Me To Your Leader ! The Great Escape into Space. - Bing, Jan; Bringsvaerd, Tor Age; Hogkvist, Stina; Maatta, Jerry (Oslo : National Museum of Art, Architecture and Design Oslo, 2010)
Aranda, Julieta ; Barbarella ; Martinson, Harry ; Dahlem, Björn ; Gallagher, Ellen ; Cleijne, Edgar ; Granö, Veli ; Ylänen, Jarmo ; Horn, Adolph Denis ; Kabakov, Ilya ; Kelley, Mike ; Kvie, Jone ; Marshall, Kerry James ; McBride, Jimmy ; McCracken, John ; McDonald, Daniel ; Melikian, Nathalie ; Plavcak, Karin ; Schweizer, Maya ; Wedemeyer, Clemens von ; Storsveen, Elise ; Ra, Sun ; Saethre, Borre ; VanDerBeek, Stan
Take Me To Your Leader ! The Great Escape into Space, National Museum of Art, Architecture and Design, Oslo, 2010-10-16. 2011-01-30
boek